(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
Today, language learning not only serves for a number of opportunities, but deep mastery of foreign languages can also serve to open the whole world. This article describes in detail the importance of grammar in teaching English in academic high schools.